2019
DOI: 10.1186/s13287-019-1183-3
|View full text |Cite
|
Sign up to set email alerts
|

Potent immunomodulation and angiogenic effects of mesenchymal stem cells versus cardiomyocytes derived from pluripotent stem cells for treatment of heart failure

Abstract: Background Optimal cell type as cell-based therapies for heart failure (HF) remains unclear. We sought to compare the safety and efficacy of direct intramyocardial transplantation of human embryonic stem cell-derived cardiomyocytes (hESC-CMs) and human induced pluripotent stem cell-derived mesenchymal stem cells (hiPSC-MSCs) in a porcine model of HF. Methods Eight weeks after induction of HF with myocardial infarction (MI) and rapid pacing, animals with impaired left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…This offers an unlimited “ off-the-shelf ” cell source with predictable therapeutic efficacy 12 , 13 . We have demonstrated that hiPSC-MSCs have better proliferative capacity, survival and therapeutic efficacy for myocardial repair than BM-MSCs 12 or embryonic stem cell-derived CMs 14 . Compared with BM-MSCs, hiPSC-MSCs are more immune-privileged due to their insensitivity to pro-inflammatory interferon -γ- induced human leukocyte antigen (HLA) class II expression 15 .…”
Section: Introductionmentioning
confidence: 92%
“…This offers an unlimited “ off-the-shelf ” cell source with predictable therapeutic efficacy 12 , 13 . We have demonstrated that hiPSC-MSCs have better proliferative capacity, survival and therapeutic efficacy for myocardial repair than BM-MSCs 12 or embryonic stem cell-derived CMs 14 . Compared with BM-MSCs, hiPSC-MSCs are more immune-privileged due to their insensitivity to pro-inflammatory interferon -γ- induced human leukocyte antigen (HLA) class II expression 15 .…”
Section: Introductionmentioning
confidence: 92%
“…Liao et al . 37 reported that transplantation of human induced pluripotent stem cell-derived mesenchymal stem cells (hiPSC-MSCs) is safe for the improvement of cardiac function in heart failure (HF). They found this is due to their immunomodulation that improves in vivo survival and enhanced angiogenesis via paracrine effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac function in each mouse was assessed by transthoracic echocardiography (Ultramark 9; Soma Technology) at baseline (before MI), 1, or 28 days following MI. LVEF and LVFS were calculated as previously described (Liao et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Over the last few decades, mesenchymal stem cell (MSC)‐based therapy has emerged as a novel alternative treatment for MI (Kim et al, 2018; Teerlink et al, 2017). Accumulating evidence has demonstrated that transplantation of MSCs can attenuate cardiac remodeling and improve heart function recovery following MI by inhibiting cardiomyocyte apoptosis, increasing angiogenesis, and rejuvenating cardiac muscle cells (Liao et al, 2019; Zhang et al, 2017, 2019). However, the functions of MSCs dramatically decline with aging, as evidenced by increased cellular senescence, impaired proliferative capacity, and decreased paracrine effects, thereby heavily limiting their cardioprotective effects following MI (Liu et al, 2014; Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%